Specifically modified Env immunogens activate B-cell precursors of broadly neutralizing HIV-1 antibodies in transgenic mice - McGuire, Andrew T. (Nat Commun, 2016)
VRC01-class broadly neutralizing HIV-1 antibodies protect animals from experimental infection and could contribute to an effective vaccine response. Their predicted germline forms (gl) bind Env inefficiently, which may explain why they are not elicited by HIV-1 Env-immunization. Here we show that an optimized Env immunogen can engage multiple glVRC01-class antibodies. Furthermore, this immunogen activates naive B cells expressing the human germline heavy chain of 3BNC60, paired with endogenous mouse light chains in vivo. To address whether it activates B cells expressing the fully humanized gl3BNC60 B-cell receptor (BCR), we immunized mice carrying both the heavy and light chains of gl3BNC60. B cells expressing this BCR display an autoreactive phenotype and fail to respond efficiently to soluble forms of the optimized immunogen, unless it is highly multimerized. Thus, specifically designed Env immunogens can activate naive B cells expressing human BCRs corresponding to precursors of broadly neutralizing HIV-1 antibodies even when the B cells display an autoreactive phenotype.